Development of an aerosol mass spectrometer lens system for PM2.5. Issue 8 (2nd August 2016) - Peck, Jay; Gonzalez, Lino A.; Williams, Leah R.; Xu, Wen; Croteau, Philip L.; Timko, Michael T.; Jayne, John T.; Worsnop, Douglas R.; Miake-Lye, Richard C.; Smith, Kenneth A.
ABSTRACT: The aerodynamic lens system of the Aerodyne Aerosol Mass Spectrometer (AMS) was analyzed using the Aerodynamic Lens Calculator. Using this tool, key loss mechanisms were identified, and a new lens design that can extend the transmission of particulate matter up to 2.5 μm in diameter (PM2.5) was proposed. The new lens was fabricated and experimentally characterized. Test results indicate that this modification to the AMS lens can significantly improve the transmission of large sized particles, successfully achieving a high transmission efficiency up to PM2.5 range. © 2016 American Association for Aerosol Research